2015
DOI: 10.7752/jpes.2015.02038
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose: determination of classification model of 7-9 years old boys' motor fitness. The methods of the research: we used the following methods of research: analysis of scientific literature data, pedagogic testing, methods of mathematical statistics. As method of simulation we used discriminant analysis. In our researches 7 boys of 7 yrs. age (n=22), 8 years. age (n=27), 9 yrs. age (n=29) participated. Results: we the calculated canonic coefficients of discriminant function (not standardized). They play r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
21
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
(21 reference statements)
3
21
0
Order By: Relevance
“…In previous works it was found that discriminant analysis can be effectively used in classification of boys and girls of secondary [23,24,28] and senior forms [21,22]. The received data point at prognostic significance of discriminant function in assessment of schoolchildren's motor and functional fitness [7].…”
mentioning
confidence: 99%
“…In previous works it was found that discriminant analysis can be effectively used in classification of boys and girls of secondary [23,24,28] and senior forms [21,22]. The received data point at prognostic significance of discriminant function in assessment of schoolchildren's motor and functional fitness [7].…”
mentioning
confidence: 99%
“…One of problems, which if faced by school physical education, is optimization of schoolchildren's training process [1,7,[25][26][27]. Works by O.V.…”
mentioning
confidence: 99%
“…One of conditions of schoolchildren's motor fitness improvement is organization of pedagogic control at physical culture lessons [4,5,6,17,19,33,34,35,36,37], in conditions of sport training 3,18,16,17,27]. Effectiveness of pedagogic control depends on the presence of object of control and informative indicators characterizing change of its state.…”
mentioning
confidence: 99%
“…Effectiveness of pedagogic control depends on the presence of object of control and informative indicators characterizing change of its state. In recent publications it has been determined that modeling is an effective method for receiving of new information concerning current and finalizing control on the base of testing of children's and adolescents' motor fitness [13,33,34,35,36,37]. One of methods of statistical modeling is factorial and discriminant analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation